Spatial correspondence between areas of concentration of Patagonian scallop (Zygochlamys patagonica) and frontal systems in the southwestern Atlantic - Bogazzi, Eugenia (2005)
It has been hypothesized that the geographical locationof scallop beds in extensive shelf regions mirrorshydrographic structures (e.g. frontal systems) thatfavor the retention/concentration of pelagic larvae.Large, discontinuous concentrations of the Patagonianscallop (Zygochlamys patagonica) are known to haveoccurred recurrently (for more than 30 yr) at certaingeographical locations over the extensive Patagonianshelf. These stocks, exploited since 1996, currentlysupport one of the most important scallop fisheries inthe world. Here, we investigate whether those aggregationsare spatially coincidental with major frontalsystems. Several pieces of information were used: historicalsurvey data documenting the geographic distributionof the Patagonian scallop beds, catch andeffort data from the commercial fleet, oceanographicdata on frontal systems, and remote sensing imagery.We found that large-scale aggregations do match thelocation of three major and very different frontal systemsin the southwestern Atlantic: the Shelf-BreakFrontal System, the Northern Patagonia Frontal System,and the Southern Patagonia Frontal System. Wedescribe the three frontal systems and their associatedscallops fishing grounds and discuss which processescan contribute to sustaining the productivity of thescallop grounds in each case.Key words: benthic fishery, frontal systems,metapopulation, Patagonian scallop, shelf-breakfront, shelf-sea front, southwestern Atlantic